50 fantastic ideas for creative role play - Hughes, Haley (London : Featherstone, 2017)
Role-play is a fun and creative way to engage with children in EYFS and is fundamental in developing children's learning and communication skills. This new addition to the 50 Fantastic series is filled with great ways to make the most of play-based learning in your environment. Each activity is linked to children's interests and is designed to allow the child to learn, create, communicate and have fun! Many of the scenarios involve an element of problem solving to encourage team work and the suggested props and locations are both easily sourced and well-suited to Early Years schools and settings. With a whole host of inspirational ideas with photos to match, this book is the perfect starting point for creating an outstanding role-play environment.
Keywords: Early childhood education -- Activity programs; Role playing in children -- Study and teaching (Early childhood) -- Activity programs; EDUCATION / Elementary